2013
DOI: 10.1177/0269758012472764
|View full text |Cite
|
Sign up to set email alerts
|

Victim satisfaction with restorative justice

Abstract: Evaluative studies have demonstrated that victims of crime are satisfied with their participation in a restorative intervention. Meanwhile, the explanation of victim satisfaction with restorative practices remains to be established. In this article, we study factors contributing to victim satisfaction with the restorative approach and ask to what extent victim satisfaction is simply due to procedural justice. Procedural justice theory predicts that the perceived fairness of a conflict resolution procedure is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 62 publications
(90 reference statements)
1
56
0
2
Order By: Relevance
“…This adat-based solution to social problems is in line with the restorative justice concept. This is in line with Van Camp &Wemmers Opinion that stated the conception of the value in restorative justice is about healing and recognition of the involved parties, such as victim, offender, and community [8]. This study proposes the presence of the informal justice institution and named as the LMA.…”
Section: The Construction Of the Madurese Legal Culture Based On The supporting
confidence: 66%
“…This adat-based solution to social problems is in line with the restorative justice concept. This is in line with Van Camp &Wemmers Opinion that stated the conception of the value in restorative justice is about healing and recognition of the involved parties, such as victim, offender, and community [8]. This study proposes the presence of the informal justice institution and named as the LMA.…”
Section: The Construction Of the Madurese Legal Culture Based On The supporting
confidence: 66%
“…The weak management system of the Department of Corrections in Indonesia brings many obstacles in realizing the treatment concept, especially for corruption inmates. At least there are three main factors which used to categorize various obstacles in the treatment issues, [13] such as (1) structure of law, (2) the substance of law; and (3) legal culture.…”
Section: Ineffectiveness Factors On Treatment System Against Inmates mentioning
confidence: 99%
“…Although victim satisfaction is considered one of the benefits of RJC, what factors lead to satisfaction with RJC remains less clear (Umbreit et al 2002;Vanfraechem and Aertsen 2010). Tyler (1990) and others (see Van Camp 2014) have suggested that the procedural processes of RJC play a large role in the satisfaction of participants in RJC, but to date there remains only a marginal amount of empirical research on this question. Armstrong (2012) interviewed 35 victims who participated in the RJC process in the United Kingdom ('UK') 4 about what factors they perceived to be important.…”
Section: Participants' Viewsmentioning
confidence: 99%